Human Papillomavirus Vaccine Frequency for University of Kansas Medical Center Pediatric Patients - Theodoro, Mariana; Demo, Andrew; Katzer, Cara; Katzer, Clinton; Shaw, Pam; Satterwhite, Catherine L. (Kansas Journal of Medicine, 2019)
Background. Human papillomavirus (HPV) vaccination is recommendedfor all adolescents aged 11 to 12 years, but coveragein Kansas is exceptionally poor. To understand local coverage, receiptof the 3-dose HPV vaccine series among pediatric patients atthe University of Kansas Medical Center (KUMC) was evaluated.Methods. All patients aged 11 to 12 years who were seen by aKUMC primary care provider (family medicine and pediatrics)in 2013 were included in the retrospective chart review. Recordswere reviewed through December 31, 2014 to capture the numberof HPV doses received, and receipt of other recommendedvaccines (tetanus-diphtheria-pertussis and meningococcal conjugate).Pearson’s chi-squared tests were used to evaluate relationshipsbetween HPV vaccination and patient characteristics.Results. Of the 261 eligible females and 243 eligible males, 71.2%received ≥ 1 HPV vaccine dose, 55.2% received ≥ 2 doses, and39.3% completed the HPV vaccine series (3 doses). Although vaccineinitiation was slightly lower in males compared to females(67.1% vs. 75.1%, p = 0.047), no difference in vaccine completionwas seen between males and females (37.0% vs. 41.7%, p = 0.319).Over 80% of patients received other concurrently recommendedvaccines (Tdap: 81.7%, meningococcal: 81.3%). HPV series completionoccurred more often among Spanish-speaking femalescompared to English-speaking females (59.5% vs 37.7%; p < 0.01).Conclusions. The proportion of adolescents who received theHPV vaccination at KUMC is substantially higher than nationaland state estimates, but there is room for improvement forboth initiation and series completion. KS J Med 2016;9(1):1-5.